Mental Health & Trauma among Incarcerated Persons: Development of a Training Curriculum for Correctional Officers - DeHart, Dana (American journal of criminal justice, 2019)
Serious mental illness and trauma among persons incarcerated in prisons and jails are issues of growing concern across the nation. This study describes a three-phase process of needs assessment, media development, and pilot testing for a comprehensive curriculum for training correctional officers on the mental health needs of persons who are incarcerated. Following the pilot training, there was a significant increase in correctional officers’ knowledge from pretest to posttest, and their ratings of course content and delivery methods were positive. The open-access, downloadable curriculum includes a PDF facilitator’s manual, participant handouts and activity cards, PowerPoint presentation slides, and brief videos or animations. The curriculum is ideally suited for delivery to correctional officers working at state and federal prisons, and may also be useful for training officers working in jails, community corrections, or other criminal justice roles.